MiR-191 promotes radiation resistance of prostate cancer through interaction with RXRA. (31st March 2020) - Ray, Jessica; Haughey, Charles; Hoey, Christianne; Jeon, Jouhyun; Murphy, Ross; Dura-Perez, Lara; McCabe, Nuala; Downes, Michelle; Jain, Suneil; Boutros, Paul C.; Mills, Ian G.; Liu, Stanley K.
Abstract: Radiation therapy is a common treatment for prostate cancer, however recurrence remains a problem. MicroRNA expression is altered in prostate cancer and may promote therapy resistance. Through bioinformatic analyses of TCGA and CPC-GENE patient cohorts, we identified higher miR-191 expression in tumor versus normal tissue, and increased expression in higher Gleason scores. In vitro and in vivo experiments demonstrated that miR-191 overexpression promotes radiation survival, and contributes to a more aggressive phenotype. Retinoid X receptor alpha, RXRA, was discovered to be a novel target of miR-191, and knockdown recapitulated radioresistance. Furthermore, treatment of prostate cancer cells with the RXRA agonist 9- cis -retinoic acid restored radiosensitivity. Supporting this relationship, patients with high miR-191 and low RXRA abundance experienced quicker biochemical recurrence. Reduced RXRA translated to a higher risk of distant failure after radiotherapy. Notably, this miR-191/ RXRA interaction was conserved in a novel primary cell line derived from radiorecurrent prostate cancer. Together, our findings demonstrate that miR-191 promotes prostate cancer survival after radiotherapy, and highlights retinoids as a potential option to improve radiotherapy response. Highlights: MiR-191 expression is elevated in prostate cancer patients with higher Gleason score. High miR-191 promotes radiation survival and targets retinoid X receptor alpha, RXRA. Treatment with the RXRA agonist 9-cis-retinoic acid restores radiosensitivity. Patients with high miR-191 and low RXRA experienced quicker biochemical recurrence.